2018
DOI: 10.1111/are.13867
|View full text |Cite
|
Sign up to set email alerts
|

Mesquite bean ( Prosopis juliflora ) meal in diets of Nile tilapia ( Oreochromis niloticus ): Nutritional value, growth, physiological responses and health

Abstract: Two experiments were conducted to assess the nutritional value and potential use of mesquite bean (Prosopis juliflora) meal (MBM) to substitute corn in extruded diets for Nile tilapia (Oreochromis niloticus). Digestible energy and the content of protein, soluble carbohydrates and amino acids were measured for 160 Nile tilapia juveniles (average weight 25.58 ± 5.52 g), allocated to eight treatment groups (four fed the experimental diet, and four fed a reference diet). To determine the inclusion potential of MBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…The author suggested that the growth and feed conversion rates were similar in control and 20% inclusion level. Conversely, more than 20% substitution of corn meal by mesquite bean ( P. juliflora ) negatively affected the growth rates and feed conversion in Nile tilapia ( Oreochromis niloticus ), as reported by De Souza et al (2019). Protein retention or apparent net protein utilization was found similar in all treatments, suggesting that KPM was well utilized by L .…”
Section: Discussionmentioning
confidence: 70%
“…The author suggested that the growth and feed conversion rates were similar in control and 20% inclusion level. Conversely, more than 20% substitution of corn meal by mesquite bean ( P. juliflora ) negatively affected the growth rates and feed conversion in Nile tilapia ( Oreochromis niloticus ), as reported by De Souza et al (2019). Protein retention or apparent net protein utilization was found similar in all treatments, suggesting that KPM was well utilized by L .…”
Section: Discussionmentioning
confidence: 70%
“…Mesquite pod meal (MPM) is the main co-product commonly used for consumption, is used in feeds for cattle, goats and sheep (Almeida et al, 2017). Recently, pod meal has been proved as nutritive source of energy and protein (Braga et al, 2010) and amino acids (Souza et al, 2018) for Nile tilapia.…”
Section: Introductionmentioning
confidence: 99%